1990
DOI: 10.1104/pp.92.4.954
|View full text |Cite
|
Sign up to set email alerts
|

Triazine Resistance in Senecio vulgaris Parental and Nearly Isonuclear Backcrossed Biotypes Is Correlated with Reduced Productivity

Abstract: Isonuclear triazine-susceptible and triazine-resistant Senecio vulgaris L. biotypes were developed by making reciprocal crosses between susceptible and resistant biotypes to obtain F1 hybrids and backcrossing the hybrids to the appropriate pollen parent. The electrophoretic isozyme patterns of the enzyme aconitase obtained from leaf extracts of triazine-susceptible parental (S) and backcrossed (SXRBC6) biotypes, and triazine-resistant parental (R) and backcrossed (RXSBC6) biotypes verified that the biotypes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 27 publications
3
24
0
2
Order By: Relevance
“…Mattoo (22) has suggested that the rapid anabolism-catabolism rate of the Dl protein could serve as a signal, resulting in the reorganization of membranes around the PSII complex. The dynamic nature of these responses has led several to conclude that the primary effect of R is complex, involves more than one aspect of photosynthesis, and can be mitigated by other processes in the system (17,23). For example, it has been pointed out that decreased QA to QB electron transport in R plants is more rapid than the normally rate-limiting oxidation of plastoquinol (4,24), whereas other studies indicate that this step may be rate limiting (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mattoo (22) has suggested that the rapid anabolism-catabolism rate of the Dl protein could serve as a signal, resulting in the reorganization of membranes around the PSII complex. The dynamic nature of these responses has led several to conclude that the primary effect of R is complex, involves more than one aspect of photosynthesis, and can be mitigated by other processes in the system (17,23). For example, it has been pointed out that decreased QA to QB electron transport in R plants is more rapid than the normally rate-limiting oxidation of plastoquinol (4,24), whereas other studies indicate that this step may be rate limiting (20).…”
mentioning
confidence: 99%
“…Inferences from these studies have been confounded because they relied on a nonisogenic model system. McCloskey and Holt (23) have suggested that nuclear genome differences may compensate for differences in productivity between nonisogenic R and S selections, and that detrimental effects may be attenuated by interactions of plastid and nuclear genomes (27). Many of these limitations may have been overcome in studies with the nearly isonuclear biotypes of B. napus (5,30).…”
mentioning
confidence: 99%
“…On the other hand, genetic similarity among accesses of Avena sterilis were studied by Heun et al (1994) who conducted a comparative analysis using RAPD molecular and enzymatic markers, and concluded that RAPD markers were highly efficient in separating the 24 biotypes tested. McCloskey & Holt (1990) also reported genetic differences between two biotypes of Senecio vulgaris (one resistant and the other susceptible to the herbicide triazine) using molecular analysis with RAPD technique. Preliminary genetic variability analysis among species and clones of Populus plants were observed by Sanchez et al (1998), using only one sequence primer.…”
Section: Resultsmentioning
confidence: 99%
“…Triazine herbicide resistance (TR) in S. vulgaris is caused by a point mutation in the psbA chloroplast gene that results in a conformation change in the D1 protein of photosystem II (Hirschberg, Bleecker, Kyle, McIntosh, & Arntzen, 1984), resulting in a less efficient electron transport through photosystem II (Arntz, DeLucia, & Jorda, 2000). The TR-mutation results in less dry mass and as much as a 20-30% reduced photosynthetic rate compared to plants with a susceptible chloroplast genome (Holt, Stemler, & Radosevich, 1981;McCloskey & Holt, 1990). Repeated use of herbicides leads to strong selection for resistance and has been reported in many weed species (Holt & LeBaron, 1990;www.weedscience.org/in.asp).…”
Section: Introductionmentioning
confidence: 99%